2018
DOI: 10.1007/s10897-018-0242-8
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Genetic Counselors from Clinical to Non‐clinical Positions: Identifying Driving Forces

Abstract: A previous study of genetic counselors (GCs) in the state of Indiana identified movement out of clinical positions within the past 2 years. The aims of this study were to determine if this trend is nationwide and identify reasons why GCs are leaving their positions and factors that might help employers attract and retain GCs. An email was sent to members of the American Board of Genetic Counseling with a link to an online confidential survey. There were 939 responses (23.5% response rate). Overall, 52% of GCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In 2008, 82% of counselors reported working in clinical settings and providing direct patient care [6], dropping to 59% in 2018 [5] and 2019 [7]. With a wider range of job opportunities in administration, research, public health, industry, and public policy [8], the number of counselors practicing in clinical settings is declining [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, 82% of counselors reported working in clinical settings and providing direct patient care [6], dropping to 59% in 2018 [5] and 2019 [7]. With a wider range of job opportunities in administration, research, public health, industry, and public policy [8], the number of counselors practicing in clinical settings is declining [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore also important to recognize the utility of GCs within leadership positions that allow them to make similarly impactful changes to their practices. Multiple respondents in this study indicated institutional barriers to delegation, and GCs in other studies have noted lack of institutional/clerical support as common reasons for leaving their clinical positions (Cohen & Tucker, ). While managerial and leadership training is not part of formal genetic counseling training, the development of this complementary expertise can create an administrator able to champion an environment where genetic counselors can function at the top of their scope of practice.…”
Section: Discussionmentioning
confidence: 62%
“…Multiple respondents in this study indicated institutional barriers to delegation, and GCs in other studies have noted lack of institutional/clerical support as common reasons for leaving their clinical positions (Cohen & Tucker, 2018…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations